Decolonizing zemiology: outlining and remedying the blindness to (post)colonialism within the study of social harm - Wright, Edward J. (Critical criminology, 2023)
This paper hosts the first meaningful dialogue between two important epistemic movements for criminology: zemiology and decolonisation. I identify that zemiology has a disciplinary blindness to colonialism and explain this using Gurminder K. Bhambra’s scholarship - and cognate scholarship - as a frame. Three cases - Pemberton’s Harmful Societies, Grenfell, and Border Zemiology - are selected for their critical importance within zemiology. They are used to argue that zemiology works within a standard narrative of modernity characterised by capitalist nation-states, which does not recognise the colonial foundations of both of these. Capitalist modernity is, however, a colonial formation. Recognising this allows for a better understanding for a wide range of harms. I then discuss future directions for decolonial zemiology, advocating not for expansion of repertoire, but canonical revision so that colonialism is afforded space as an explanatory frame and zemiology can better explain social harm on a global level.